Efek Pemberian Kombinasi Siprofloksasin dan A-Mangostin Secara In Vitro Terhadap Eradikasi Uropatogen Escherichia Coli - Rakhmawatie, Maya Dian; Rohmani, Afiana (Universitas Muhammadiyah Semarang, 2015)
Effect of In Vitro Combination of Ciprofloxacin and A-Mangostin on Eradication of Uropathogen Escherichia ColiBackground: The percentage of resistance Escherichia coli (E. coli) in patients with UTI to ciprofloxacin reached 73.04%. Various attempts to maximize the use of antibiotics have been done, including optimizing the parameters pharmacokinetics/pharmacodynamics (PK / PD) of each antibiotic. Another effort is needed to optimize the use of antibiotic treatment that has been available, one of which combines the use of compounds derived from herbs, eg active compounds a-mangostin.Objective: The purpose of this study is to find the effect of the combination of á-mangostin and ciprofloxacin on uropathogen E. coli (UPEC) eradication.Methods: This research was carried out by treating the bacteria uropathogenE. coli (UPEC) in vitro. Treatment is divided into (a) treatment groups using ciprofloxacin concentration Cmax at 500 mg dose (2,4 μg/mL), (b) treatment groups using ciprofloxacin concentration Cmax at 750 mg dose (4,3 μg/mL), (c) treatment groups using ciprofloxacin concentration 2,4 μg/mL and a-mangostin concentration 0,18 μg/mL, (d) treatment groups using ciprofloxacin concentration 4,3 μg/mL and a-mangostin concentration 0,18 μg/mL.Result: states that a combination of á-mangostin and ciprofloxacin can prevent the growth of uropathogen E. coli ciprofloxacin-resistant strains (MIC value of 128 μg/mL) compared to administration of ciprofloxacin alone, but the effect was not significant. On uropathogen E coli sensitive to ciprofloxacin (MIC 0,008 μg/mL) and intermediate (MIC 0,5 μg/mL), there was no difference effect of decreasing the number of colonies between awarding a combination of ciprofloxacin and á-mangostin compared administering ciprofloxacin only.Conclusion: Provision of á-mangostin grading 0,18 μg/mL combined with ciprofloxacin had no real benefit in eradicating uropathogen E. coli, which is tested in vitro.